Long-term soiling of silicon PV modules in a moderate subtropical climate. (June 2016) - Lopez-Garcia, Juan; Pozza, Alberto; Sample, Tony
Highlights: Long-term soiling effects in PV modules exposed in a moderate subtropical climate. Manual cleaning effective at improving the output of all the module types. Additional high pressure water showed small improvements on textured glass modules. Overall average improvement in P max after all cleaning processes of 9.8%. Low average annual soiling rate (0.31% in P max ) due to high annual precipitation. Abstract: The results of 28 silicon-based PV modules which were installed from 1981 to 1985 in a free rack configuration in the outdoor test facility of the European Solar Test Installation (ESTI) and dismantled at the end of 2014 without cleaning were analysed. The system was composed of modules with two series-connected laminates mounted in a single frame produced by the same manufacturer but using different cell layouts and cover glasses (plain glass or textured glass). The effects of long-term soiling on the PV module performance for more than 30 years of outdoor exposure in a moderate subtropical climate and the influence of different cleaning methods from manual cleaning to the use of high pressure water washing were investigated. The influence of the cover glasses and the mismatch due to the particular manufacturing design were also analysed. It was observed that a manual cleaning was effective at improving the output of all the module types. However, additional high pressure water spraying on plain glass modules showed no further improvement, but showed small improvements on the textured glass modules. Overall improvements in P max after cleaning ranged from 3.5% to 19.4%, with an average value of 9.8% and an average improvement in I sc of 6.7% were obtained.